Important Medicinal Plant Families in Thailand - Methee Phumthum; Henrik Balslev; Anders S. Barfod (Frontiers Media S.A., 2019)
Throughout the world, surveys have been conducted at the country level to answer research questions pertaining to ethnomedicinal usage patterns. This study is focused on Thailand, which has never been surveyed systematically in this way. We mined 16,000 records of medicinal plant use from 64 scientific reports, which were published from 1990 to 2014. In total, 2,187 plant species were cited as being useful for medicinal purposes. The overall aim was to reveal the relative importance of the plant families for pharmacological research. To determine the most important medicinal plant families, we use a combination of three statistical approaches: linear regression, Binomial analysis, and Bayesian analysis. At the regional level, 19 plant families repeatedly stood out as being the most important from an ethnomedicinal perspective.